HBsAg AND HCV: INCREASING TEST REQUESTS AND DECREASING FREQUENCY OF POSITIVE TESTS AT CLINICAL LABORATORY OF AYUB TEACHING HOSPITAL, ABBOTTABAD - Ally, Sirajuddin Hassan; Hanif, Ruhila; Ahmed, Ayesha (Journal of Ayub Medical College Abbottabad, 2005)
Background: This audit was carried out to assess the frequency of positive results out of the total test requests made for HBsAg and HCV at our laboratory. The frequencies for three years were compared for significance. We have reported monthly total test requests and frequency of positive tests for each of these years in this article. Methods: This study is an audit of all HBsAg and HCV test requests received at clinical laboratory of Ayub Teaching Hospital, Abbottabad during a three year period from 2002-2004. Both the tests were made using Rapid device (immunochromatographic kits) method. Frequencies of positive results were calculated from the total test requests for each month of these three years. Cumulative frequencies were compared for statistical significance of difference. Results: Total HBsAg tests requested for years 2002, 2003 and 2004 were 2058, 2563 and 5207 respectively. The frequencies of HBsAg positive cases out of these were 5.53%, 4.36% and 2.68% respectively. The number of test requests for HBsAg increased significantly from 2002 to 2003 and 2004, while the frequency of positive tests decreased significantly (p<.001) during this period. Total HCV requests for years 2002, 2003 and 2004 were 1261, 1671 and 4638 respectively. The frequencies of HCV positive cases out of these were 14.19%, 8.79% and 5.84% respectively. Just like HBsAg, number of test requests for HCV increased significantly from 2002 to 2003 and 2004, while the frequency of positive tests decreased significantly (p<.001) during this period. Conclusions: The test requests have considerably increased in the last few years, probably as a result of increasing awareness of clinicians and public. However most of these tests are negative. In view of high prevalence of both HBsAg and HCV in Pakistan, this overcautious attitude of clinicians is understandable although this is a burden on the pocket of patients and hospital resources. Keywords: HBsAg, HCV, Microbiology, Audit, Clinical laboratory